Time-dependent deformation behavior of freestanding and SiNx-supported gold thin films investigated by bulge tests. Issue 14 (13th July 2015) - Merle, Benoit; Cassel, Detlev; Göken, Mathias
Abstract: Abstract : A novel strain-rate jump method was developed for the plane-strain bulge test and used to investigate the time-dependent deformation behavior of gold thin films in the thickness range 100–400 nm. The experimental method is based on an abrupt variation of the pressurization rate. The evaluated strain-rate sensitivity was found to be five times higher for films in freestanding condition ( m = 0.094) than for films tested on a SiN x substrate ( m = 0.020). Bulge creep tests confirmed this increased time-dependence. The observation of the surface of the freestanding films after the creep tests provided evidence of apparent grain boundary sliding taking place next to intragranular plastic deformation. The out-of-plane deformation was presumably favored by the columnar microstructure of the samples, with grains extending between both free surfaces. In the case of SiN x -supported films, grain boundary sliding was prevented by the good adhesion of gold to the SiN x substrate.